The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1089/lap.2014.0582
|View full text |Cite
|
Sign up to set email alerts
|

One-Session Laparoscopic Management of Combined Common Bile Duct and Gallbladder Stones Versus Sequential ERCP Followed by Laparoscopic Cholecystectomy

Abstract: The single-session laparoscopic management of CBD stones is as safe and effective as the gold standard sequential ERCP followed by LC with nearly the same rate of success, hospital stay, and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In the study of Mohamed et al, 87% presented with acute biliary pain with jaundice, 8% presented with acute pancreatitis while 6% presented only with jaundice. 11 Tan et al reported the initial presentations of 60.0% with right hypochondrial pain and 46.0% with jaundice. Acute cholangitis accounted for 32% of the emergency presentations, followed by acute pancreatitis in 10.0% and acute cholecystitis in 10.0%.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Mohamed et al, 87% presented with acute biliary pain with jaundice, 8% presented with acute pancreatitis while 6% presented only with jaundice. 11 Tan et al reported the initial presentations of 60.0% with right hypochondrial pain and 46.0% with jaundice. Acute cholangitis accounted for 32% of the emergency presentations, followed by acute pancreatitis in 10.0% and acute cholecystitis in 10.0%.…”
Section: Discussionmentioning
confidence: 99%
“…None of the 25 studies reported mean BMI. Only one study 20 reported the preoperative laboratory investigation (median (range) bilirubin concentration for LTCE 20 (6-74) μmol/l and Reference Gigot et al 31 Millat et al 34 Arvidsson et al 20 Martin et al 33 Lauter and Froines 24 Tokumura et al 40 Waage et al 42 Jameel et al 22 Zhang et al 19 Hongjun et al 18 Aawsaj et al 28 Overall Heterogeneity: 31 Arvidsson et al 20 Martin et al 33 Lauter and Froines 24 Tokumura et al 40 Waage et al 42 Zhang et al 19 Overall Phillips et al 36 Millat et al 34 Berthou et al 29 Michel et al 25 Topal et al 41 Tan et al 39 Santo et al 38 Mohamed et al 35 Rhodes et al 37 Cuschieri et al 30 Phillips et al 36 Gigot et al 31 Millat et al 34 Berthou et al 29 Martin et al 33 Tokumura et al 40 Waage et al 42 Jameel et al 22 Tai et al 23 Tan et al 39 Zhang et al 19 Aawsaj et al 28 Overall Hongjun et al 18 Berthou et al 29 Martin et al 33 Overall Hongjun et al 18 Reference...…”
Section: Resultsmentioning
confidence: 99%
“…The median quality score for the RCTs was judged based on the Cochrane Handbook 13 . The quality assessment stratifies the current evidence and projects the need for further research on the topic based on the quality of the available evidence into: high-quality evidence where further research is not expected to change the current confidence in the estimate of the effect size, moderate-quality evidence if further research is likely to influence confidence in the estimated effect and may change it; low-quality evidence if further research is very likely to influence confidence in the estimate of Reference Design n-RCT Phillips et al 36 Gigot et al 31 Millat et al 34 Arvidsson et al 20 Berthou et al 29 DePaula et al 27 Martin et al 33 Lauter and Froines 24 Michel et al 25 Tokumura et al 40 Waage et al 42 Topal et al 41 Jameel et al 22 Tan et al 39 Santo et al 38 Dimov et al 26 Darrien et al 21 Mohamed et al 35 Zhang et al 19 Aawsaj et al 28 Rhodes et al 37 Cuschieri et al 30 Grubnik et al 32 Overall n-RCT heterogeneity: I 2 = 68%, P < 0·05 RCT heterogeneity: I 2 = 72% P < 0·05 Heterogeneity: 2 Forest plot for successful duct clearance in patients with choledocholithiasis undergoing a laparoscopic transcystic or transcholedochal approach. Studies that had 100 per cent success in both arms 18,23 were not included in the analysis, so calculation of an odds ratio was not possible in the pooled analysis.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…This two-stage approach has some disadvantages, including the risk of CBD stone passage taking place between ERCP and LC or during LC due to excessive gallbladder handling. These potential problems can be avoided by using the single-session laparoscopic approach for managing CBD stones during LC by transcystic exploration (TCE) or laparoscopic CBD exploration (LCBDE), which is as safe and effective as the ‘gold standard’ sequential ERCP followed by LC with the nearly same rate of success, length of hospital stay, and rate of complications [ 10 ]. In this study, we used a trans-gastrointestinal tract cholecystoscopy technique in treating GB disease without cholecystectomy, which may be superior in reduction of residual scarring and in preserving of gallbladder function.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to evaluate this trans-gastrointestinal tract cholecystoscopy technique in treating gallbladder (GB) disease without the need for cholecystectomy. We also combined both endoscopic sphincterotomy (EST) and cholecystolithotomy into a one-session treatment for those patients who have both gallstones and common bile duct stones, which could potentially become another popular alternative to LC plus LCBDE [ 10 ].…”
Section: Introductionmentioning
confidence: 99%